Pelayanan Pembuatan Akta Kelahiran Di Kabupaten Subang - Wawan Setiawan Abdilah; Puji Fitriani Abdullah (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2020)
According to the data gained by researchers from the Department of Population and Civil Registration in Subang, there are still the number of children aged 0 to 18 years who do not owna Birth Certificate. In 2018, the Subang Population and Civil Registry Service set a target of 85%, where children in Subang Ages 0 to 18 years must own a Birth Certificate. However, there are lots of obstacles to realizing this target, both from service and the community. The research method used in this study is qualitative approach. In this study, researchers used a descriptive research type so that it would be described how effective the service of making Birth Certificates for Children aged 0 to 18 years in the Population and Civil Registry Office of Subang. In order to get data and information, The techniques that the researchers did are through observation and interviews. The results of the research in the field show that the effectiveness of birth certificate making services in the context of fulfilling the identity of children aged 0 to 18 years in Subang in terms of service is very optimal but there are obstacles from the community.